2019
DOI: 10.5194/isprs-annals-iv-5-w2-49-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sar – Optical Remote Sensing Based Forest Cover and Greenness Esti-Mation Over India

Abstract: Abstract. Indian natural forest has a high ecological significance as it holds much biodiversity and is primarily affected due to deforestation. The present study exhibits the forest cover change on Global Forest Non-Forest (FNF) data for India and greenness trend using MOD15A2H LAI product, which is the best product available till date. JAXA uses of SAR datasets for forest classification based on FAO definitions. Later, Forest Survey of India (FSI) used different definitions for forest classification from FAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Results revealed a significant positive correlation of 0.67 between the MODIS LAI and LAI derived from the aggregated LISS-III data set. Lal et al (2019) also considered the MODIS LAI collection 6 data product (MOD15A2H) to diagnose the forest cover change and greenness trend over the Indian region after the validation of this data product by Yan et al (2016) at a global scale. Yan et al (2016) found that the MODIS LAI collection 6 product (MOD15A2H) is the highest quality LAI product available to-date based on the validation of this product against the ground-based measurements and an intercomparison with other satellite products.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed a significant positive correlation of 0.67 between the MODIS LAI and LAI derived from the aggregated LISS-III data set. Lal et al (2019) also considered the MODIS LAI collection 6 data product (MOD15A2H) to diagnose the forest cover change and greenness trend over the Indian region after the validation of this data product by Yan et al (2016) at a global scale. Yan et al (2016) found that the MODIS LAI collection 6 product (MOD15A2H) is the highest quality LAI product available to-date based on the validation of this product against the ground-based measurements and an intercomparison with other satellite products.…”
Section: Datamentioning
confidence: 99%
“…Lal et al. (2019) also considered the MODIS LAI collection 6 data product (MOD15A2H) to diagnose the forest cover change and greenness trend over the Indian region after the validation of this data product by Yan et al. (2016) at a global scale.…”
Section: Datamentioning
confidence: 99%
“…Such extreme measures to control the virus have potentially resulted in decreases of aerosols and atmospheric pollutants due to the disruption of anthropogenic-based emissions (https://www.theguardian.com/ world/2020/mar/20/coronavirus-the-week-the-world-shut-down). Aerosols have direct and indirect contributions on climate change at regional and global scales (Huang et al, 2014;Menon et al, 2002;Qian and Giorgi, 1999) as increased levels of Aerosol Optical Depth (AOD) affects atmospheric stability and precipitation as aerosols disturb the scattering and absorption of solar radiation (Jiang et al, 2016), the hydrological cycle (Prasad et al, 2004) and vegetation cover and its growth (Lal et al, 2019;Sarkar and Kafatos, 2004). In addition to climatic effects, aerosols increase respiratory problems in humans and decrease visibility in urban areas (Prasad et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Countless studies have already unveiled the importance of aerosol research, and also demonstrated the direct and indirect contributions of aerosols on the climate change at regional to global scales ( Qian and Giorgi, 1999 ; Menon, 2002 ; Huang et al, 2014 ). The aerosol optical depth (AOD) affects the atmospheric stability and precipitation as aerosols disturb the scattering and absorption of solar radiation ( Jiang et al, 2016 ; Shaw and Gorai, 2018 ), the hydrological cycle ( Prasad et al, 2004 ), and vegetation cover and its growth ( Lal et al, 2019 ; Sarkar and Kafatos, 2004 ). Apart from climatic effects, aerosol causes many serious health-related issues (i.e., asthma, premature death, lung cancer, cardiopulmonary mortality, and pulmonary inflammation) ( Prasad et al, 2005 ; Huang et al, 2012 ; Mulenga and Siziya, 2019 ).…”
Section: Introductionmentioning
confidence: 99%